2021
DOI: 10.3390/app11188610
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Murta (Ugni molinae Turcz) Powder on the Frankfurters Quality

Abstract: Frankfurters are one of the most demanded meat products in the world due to their low cost and good taste. However, they contain up to 30% animal fat, which is negative for the consumer’s health. Moreover, high-fat contents could also decrease frankfurter sensory properties, since it accelerates the rancidity of the products. This fact is highly dependent on the fatty acids composition since the unsaturation promotes oxidative reactions. Currently, strategies have been developed to replace animal fat with vege… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…Moreover, in a more recent study, the same research group evaluated both extracts in lamb beef patties with fat replacement by chia oil hydrogel emulsion, and concluded that the use of 250 ppm of each extract is effective against color deterioration and lipid and protein oxidation, without impairing the sensorial characteristics, representing a promising alternative to replacing synthetic antioxidants by natural products in lamb beef patties [ 21 ]. The replacement of synthetic antioxidants linked to health damage by plant polyphenols with antioxidant, antimicrobial, and therapeutic potentials has been widely studied [ 11 , 13 , 22 ]. To this end, the impact of several plant extracts on the storage quality of meat products has been studied [ 21 , 22 , 23 ], however, the effect of Maqui on the storage stability of meat products has not been reported and requires scientific attention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, in a more recent study, the same research group evaluated both extracts in lamb beef patties with fat replacement by chia oil hydrogel emulsion, and concluded that the use of 250 ppm of each extract is effective against color deterioration and lipid and protein oxidation, without impairing the sensorial characteristics, representing a promising alternative to replacing synthetic antioxidants by natural products in lamb beef patties [ 21 ]. The replacement of synthetic antioxidants linked to health damage by plant polyphenols with antioxidant, antimicrobial, and therapeutic potentials has been widely studied [ 11 , 13 , 22 ]. To this end, the impact of several plant extracts on the storage quality of meat products has been studied [ 21 , 22 , 23 ], however, the effect of Maqui on the storage stability of meat products has not been reported and requires scientific attention.…”
Section: Introductionmentioning
confidence: 99%
“…The replacement of synthetic antioxidants linked to health damage by plant polyphenols with antioxidant, antimicrobial, and therapeutic potentials has been widely studied [ 11 , 13 , 22 ]. To this end, the impact of several plant extracts on the storage quality of meat products has been studied [ 21 , 22 , 23 ], however, the effect of Maqui on the storage stability of meat products has not been reported and requires scientific attention. Additionally, the use of natural antioxidants from endemic leaves in the reformulation of meat products, such the case of the present study, was extensively discussed in a recent review [ 24 ].…”
Section: Introductionmentioning
confidence: 99%